La Dislexia y su incidencia en el proceso de aprendizaje del cuato año de educación básica paralelo A de la Unidad Educativa Narciso Cerda Maldonado durante el año lectivo 2016-2017 - Mancero Lucio, Jennifer Estefanía (2017)
At present, education is constantly changing, which is why it is necessary to look for new options in the learning process, specifically for the students who suffer problems in the assimilation of new knowledge, produced in some cases by dyslexia, biophysical alteration that consists of the confusion of the letters affecting the literacy and therefore the academic performance. The main objective of the research is to strengthen the learning process in the learners, employing appropriate techniques, to allow to identify the factors that cause the disorder of dyslexia and its incidence in the integral formation of the children of the Educational Unit Narciso Cerda Maldonado. For the development of the research, methodological tools and techniques were used, such as the survey itself, which allowed us to obtain information for the preparation of a proposal to mitigate the identified problem, corresponding to the scarce application of techniques and activities to attend to the problems of dyslexia and to improve the teaching process of the students of the fourth year of the campus under analysis. The results obtained through the research, determined the need to develop a methodological guide, to train teachers and the active participation of parents, who as direct actors of the educational process must contribute significantly in learning and strengthening the skills and abilities of students, contributing to improve their academic level, specifically in dyslexic girls and boys.